Pentad wise variability in heat use efficiency (HUE) of wheat (Triticum aestivum L.) during different sowing windows under Punjab conditions - Sharma, Ambika; Singh, Sompal; Kingra, P K (Journal of Cereal Research, 2024)
Owing to lack of work on variability in heat use efficiency (HUE) of wheat (Triticum aestivum L.) under Punjab conditions, the present study was carried out. The study used long term wheat yield, temperature data from 1990-2018 and phenological data of a field trial conducted during Rabi season of 2019-2020 at research farm of Punjab Agricultural University (PAU), Ludhiana with wheat variety Unnat PBW 343 and five dates of sowing (D1-25th October, D2-5th November, D3-15th November, D4-25th November and D5-5th December. Pentad wise analysis revealed that under all sowing windows, maximum variability in heat use efficiency was observed during P5 (2010-2014) and minimum during P1 (1990-1994). And among different sowing windows, highest value of HUE (3.2 kg/ha/˚C day) was noticed under sowing window V, during P5 and lowest (2.3 kg/ha/˚C day) under sowing window II, during P1. The study concluded that increasing variability of HUE warns about more warming scenarios in future and thus, creating a strong need to develop climate smart adaptation strategies.